Embedded Control System of DC Motor Using Microcontroller Arduino and PID Algorithm - Alfian Ma'arif; Naufal Rahmat Setiawan; Eka Suci Rahayu (IT Journal Research and Development, 2021)
The development of technology has a positive effect on the trade sector, creating smartphones that can be utilized in all activities combined with the internet network. Activity that is currently growing is a mobile trader in the city of Pekanbaru. This development caused much competition, for example, in the Pekanbaru city area, especially in Sialangmunggu village. Traders around is difficult to find consumers because consumers do not have precise location and time information. Therefore, researchers aim to design and build applications by utilizing the functions of google maps and GPS (Global Positioning System) where the Algorithm to be applied is the A* algorithm whose function is to find the nearest location between buyers to mobile merchants, to accommodate data from mobile merchants where buyers can know the nearest position of the traveling merchant. Process analysis will be divided into running analysis that discusses the workings of the process of mobile traders and buyers in the field. Then the proposed system analysis of the analysis will be made by the author to maximize the process on the current analysis. By making analysis and design, the author will know the needs needed in the creation of the system. The result of using method A* is applied to displaying the merchant's route with the user, and the result can provide the fastest route to get to the trader. The use of method A* is also done to find the trader whose location is closest to the user's location, and the result can display the nearest trader.